2022
DOI: 10.1097/mao.0000000000003773
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Complaints Impact on the Long-Term Quality of Life of Vestibular Schwannoma Patients

Abstract: ObjectiveTo analyze the effect of dizziness-related symptoms on the long-term quality of life (QoL) of patients with unilateral vestibular schwannoma.MethodsIn this cross-sectional study, patients with a unilateral vestibular schwannoma diagnosed between 2004 and 2013 completed a disease-specific QoL questionnaire (Penn Acoustic Neuroma Quality of Life [PANQOL]) and the Dizziness Handicap Inventory (DHI) in 2020. Linear regression was performed to assess the correlation between QoL and the DHI total score, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A strong relationship exists between the degree of dizziness and quality of life among patients with VS [45][46][47]. In our study, individual symptoms, such as the degree of dizziness or limitations in daily life, were elusive factors that can be important in future studies.…”
Section: Plos Onementioning
confidence: 74%
“…A strong relationship exists between the degree of dizziness and quality of life among patients with VS [45][46][47]. In our study, individual symptoms, such as the degree of dizziness or limitations in daily life, were elusive factors that can be important in future studies.…”
Section: Plos Onementioning
confidence: 74%
“…It is hypothesized that this is the effect of central compensation. However, it has been reported that a proportion of VS patients suffer from vestibular symptoms in the long term, impacting on their long-term quality of life [ 2 ]. This may be because the vestibular compensation is insufficient, or because of other factors that affect dizziness and balance in this patient group.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic posturography seems to correlate with the tumor size and canal paresis (2). Other factors may confuse the analysis or even hinder central vestibular compensation in patients with comorbidities such as diabetes, hypertension, smoking, alcohol consumption, and depression, which were not evaluated in the study by Fuentealba-Bassaletti et al (1).…”
mentioning
confidence: 99%
“…To the Editor : We read with interest the article recently published by Fuentealba-Bassaletti et al (1) titled “Vestibular complaints impact on the long-term quality of life of vestibular schwannoma patients” in the issue of Otology & Neurotology .…”
mentioning
confidence: 99%